The Utilization of Indigofera sp as the sole foliage in goat diets supplemented with high carbohydrate or high protein concentrates - Ginting, Simon P; Krisnan, Rantan; Sirait, Juniar; ., Antonius (Indonesian Journal of Animal and Veterinary Sciences, 2010)
Indigofera sp is a tree leguminous forage species known to be adaptable to the drought climate and saline soil and so it has potential as alternative feed resource to support the ruminant animal production. This study aimed to study the  responses of goats fed Indigofera sp as the sole foliages in their diets. Twenty male Boer x Kacang crossbred goats  (6 months of age;16 ± 2,1 kg BW) were randomly assigned to four dietary treatments containing fresh or wilted leaves of Indigifera sp. as the sole foliages and supplemented with high carbohydrate (HCC) or protein (HPC)concentrates. Consumable parts i.e. leaves and twigs of about 8 to 10 months of age of Indigofera sp. were harvested by hand plucking every day in the morning. The experiment was a 2 x 2 factorial design arranged in a completely randomized design. The ruminal pH ranged from 6.14-6.85 and were  not affected (P > 0.05) by wilting nor by the type of concentrates. Wilting did not affect (P > 0.05) the concentration of  ruminal NH3-N, but  it was significantly higher (P < 0.05) in HPC group (32.36-32.54 mg dL-1) than those in HCC group(17.94-23.57 mg dL-1). Total VFA concentration were not affected by wilting  nor by the type of concentrates  (P > 0.05). Goats in the HCC group,however,numerically have higher total VFA concentration (178.5-183.75 mmol L-1) than those in the HPC group (142.21-174.64 mmol L-1). The apparent digestibility coeficients  of DM, OM, CP and energy of the diet were not different (P > 0.05) when contained wilted or fresh Indigofera foliage.  Significant increases (P < 0.05)   in the DM and  OM, but not in the CP and energy  apparent digestibility coeficients were observed in the HPC goats. Dry matter intakes were not different (P > 0.05) among dietary treatments, but the ADG of goats in the HCC group (60-63 g d-1) were significantly lower (P < 0.05) than those  of goats in the HPC treatment (80-87 g d-1). Blood glucosa concentration was not affected by wilting nor by type of concentrates (P > 0.05).  BUN was not affected by wilting process, but providing high protein concentrates significantly (P < 0.05) increased the BUN concentration. It is concluded that foliage of Indigofera sp could be used as the sole forage in intensive production of goats. Wilting the foliage prior to feeding seemed to be unnecessary, since this process does not improve the animal productivity in term of daily gain and efficiency of feed utilization. Key Words: Indigofera sp, Supplements,  Ruminal Fermentation, Goats